Unexpected Subjects Intimate Partner Violence, Testimony, and the Law - Gribaldo, Alessandra (HAU Books, 2021)
Unexpected Subjects is an ethnography of the encounter between women's words and the demands of the law in the context of adjudications on intimate partner violence. A study of institutional devices, it focuses on women's practices of resistance and the elicitation of intelligible subjectivities. Using Italy as an illustrative case, Alessandra Gribaldo explores the problematic encounter between the need to speak, the entanglement of violence and intimacy, and the way the law approaches domestic violence. On this basis, she advances theoretical reflections on questions of evidence, persuasion, and testimony, and their implications for ethnographic theory. Gribaldo analyzes dynamics that create the victim-subject, shedding light on how the Italian legal system reproduces broader conditions of violence against women. This book will be of great interest to all social scientists concerned with gender and the law.